Inflow Uncertainty in Hydropower Markets - Petter Vegard Hansen (Statistics Norway, Research Department, 2007)
In order to analyse the consequences of uncertainty for prices and efficiency in a hydropower system, we apply a two-period model with uncertainty in water inflow. We study three different market structures, perfect competition, monopoly and oligopoly and stress the importance of the shape of the demand function under different distributions of water inflow. The uncertainty element creates possibilities of exercising market power depending on the distribution of uncertainty among producers. The introduction of thermal power into the hydropower market has an impact on the residual demand function, which is important for the hydropower producers' possibilities of exercising market power.
Keywords: D40; Q11; Q41; L10; 330; hydropower; uncertainty; electricity; thermal power; demand functions; monopoly; duopoly